Traumatic Optic Neuropathy (TON) yang disertai edema makula dan perdarahan vitreus akibat trauma tumpul berulang pada wajah: case report - Muchamad Fadil; Lina Puspita Hutasoit; Jodii Arlan Kurnia (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Traumatic optic neuropathy (TON) is an uncommon complication of trauma that may result in severe and permanent visual impairment. Most cases are associated with major head trauma, whereas TON secondary to assault or apparently minor facial trauma is less frequently reported. We report the case of a 26-year-old man who presented with decreased vision in the left eye accompanied by an early visual field disturbance after sustaining repeated blunt trauma in the form of slaps to the left side of the face. External ocular and anterior segment examinations were unremarkable. Initial visual acuity in the left eye was 1/300, with only hand motion perception. Ocular ultrasonography revealed vitreous hemorrhage, while optical coherence tomography (OCT) demonstrated macular edema. Based on the clinical and ancillary findings, the patient was diagnosed with suspected left traumatic optic neuropathy associated with macular edema and vitreous hemorrhage. The patient was treated with local corticosteroid injection, high-dose oral methylprednisolone followed by tapering, and oral citicoline. On follow-up, visual acuity improved gradually to 5/45, accompanied by improvement of the macular appearance on OCT. This case highlights that apparently mild blunt facial trauma may still be associated with severe visual impairment suggestive of TON, even in the absence of obvious external ocular findings. Comprehensive ophthalmic examination and appropriate ancillary investigations are important to identify associated posterior segment involvement and to monitor clinical outcomes